2010
DOI: 10.1002/hipo.20906
|View full text |Cite
|
Sign up to set email alerts
|

7,8‐dihydroxyflavone, a TrkB receptor agonist, blocks long‐term spatial memory impairment caused by immobilization stress in rats

Abstract: Post-traumatic stress disorder (PTSD) patients show cognitive deficits, but it is unclear whether these are a consequence of the pathology or a pre-existing factor of vulnerability to PTSD. Animal models may help to demonstrate whether or not exposure to certain stressors can actually induce long-lasting (LL; days) impairment of hippocampus-dependent memory tasks and to characterize neurobiological mechanisms. Adult male rats were exposed to 2-h immobilization on boards (IMO), a severe stressor, and spatial le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 43 publications
7
78
0
1
Order By: Relevance
“…All samples to be statistically compared were run in the same assay to avoid inter-assay variability. Plasma corticosterone levels ( Figure 1) were determined by doubleantibody radioimmunoassay as previously described (Andero et al, 2012). Corticosterone radioimmunoassay used 125 I-corticosteronecarboximethyloximetyrosine-methyl ester (ICN-Biolink 2000, Barcelona, Spain), synthetic corticosterone (Sigma, Barcelona, Spain) as the standard, and an antibody raised in rabbits against corticosteronecarboximethyloxime-BSA kindly provided by Dr G. Makara (Institute of Experimental Medicine, Budapest, Hungary).…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…All samples to be statistically compared were run in the same assay to avoid inter-assay variability. Plasma corticosterone levels ( Figure 1) were determined by doubleantibody radioimmunoassay as previously described (Andero et al, 2012). Corticosterone radioimmunoassay used 125 I-corticosteronecarboximethyloximetyrosine-methyl ester (ICN-Biolink 2000, Barcelona, Spain), synthetic corticosterone (Sigma, Barcelona, Spain) as the standard, and an antibody raised in rabbits against corticosteronecarboximethyloxime-BSA kindly provided by Dr G. Makara (Institute of Experimental Medicine, Budapest, Hungary).…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…Two hours after the last administration, the mice were subjected to behavioral testing. The dosage of 5 mg/kg 7,8-DHF and a 2-h interval between the last drug treatment and assays were chosen on the basis of previous in vivo studies (Andero et al, 2010;Andero et al, 2011;Jang et al, 2010;Liu et al, 2010), which demonstrated central TrkB activation, enhanced neurogenesis, and related behavioral changes in mice or rats treated with systemic 7,8-DHF administration.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…Remarkably, systemic administration of 7,8-DHF can activate TrkB receptors in brains as evidenced by increases in phosphorylated TrkB, and induce BDNF-like behavioral phenotypes such as enhanced learning and memory, and antistress or antidepressant-like effects in rodents (Andero et al, 2010;Andero et al, 2011;Choi et al, 2010;Jang et al, 2010;Liu et al, 2010). Therefore, the small-molecule TrkB receptor agonist 7,8-DHF represents a novel and useful tool to investigate the role of BDNFTrkB signaling in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This stressor has been extensively characterized in our laboratory (Belda et al, 2008b) and has been determined to induce changes in activity and anxiety that can last for some days (Belda et al, 2008a), as well as more protracted impairment of spatial memory in the Morris water maze (Andero et al, 2012) and fear extinction (Andero et al, 2011).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…group in rats (i.e., Andero et al, 2012;Belda et al, 2008a;Belda et al, 2012;, Daviu et al, 2014Gagliano et al, 2008;Muñoz-Abellán et al, 2008;Muñoz-Abellán et al, 20011) and mice (Amador-Arjona et al, 2010;Andero et al, 2011).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%